VD_FINDINFO Décision / 2013 / 8 vom 4. Juli 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE, PROPORTIONNALITÉ, PROLONGATION | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 237 CPP (CH)